DESIGN OF DISASTER RECOVERY PLAN BASED ON FRAMEWORK NIST 800-34 : CASE STUDY AT PT XYZ OF INDONESIA - Waluya, Dimas Prihadi; Surantha, Nico (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
The purpose of this study to identify Risk assessment in information systems at PT XYZ using the method Octave Allegro and develop Disaster Recovery Plan on the information system at PT XYZ using the NIST 800:34 framework. The downtime on information system that occurred resulted in the disruption of business processes and operations of PT XYZ which currently has 7 main information systems to support the company's business which if not addressed can result in a decrease in user confidence in the company. In this study, a risk assessment will be carried out on information assets owned by PT XYZ using the Octave Allegro method to identify threats to information assets along with the order of threat priority. Then the design of the Disaster Recovery Plan on the information system uses the NIST 800:34 framework containing recovery steps, backup strategies and RPO RTO which are used as priority parameters for information system recovery.